Pentingnya Dukungan Suami bagi Ibu Remaja dalam Mencegah Depresi Perinatal di Puskesmas Putri Ayu Kota Jambi - Kusuma, Ratu (Jurnal Abdimas Kesehatan (JAK), 2025)
Riskesdas 2018 recorded 2,867 pregnancies aged 10-19 years and 15 of them were aged 10-14 years. Medical Records of the KIA Program and PKPR Program of Putri Ayu Health Center reported that teenage pregnancies are always increasing. In 2020 (63 people), 2021 (105 people), 2022 (August alone there were 30 people); and in 2023 (57 people). This increase is thought to be related to free sex, pregnancy outside of marriage, dropping out of school; drug use; low education; lack of information about the dangers of teenage pregnancy; and poverty factors. From the results of the interview, it was found that 2 teenage mothers showed symptoms of depression (less communicative, locking themselves in their rooms, refusing to eat, rarely bathing, pale, dirty clothes, smelly body, messy hair and less concern about pregnancy). Interviews were also conducted with 4 other teenage mothers (2 pregnant out of wedlock; aged 16-19 years; elementary-high school; received bad treatment from husbands such as domestic violence, cheating, not having a permanent job, not providing material support, spending time with friends, being indifferent to children and wives, and not helping with housework). These various problems pose a risk of emotional disorders such as perinatal depression. Education was carried out on June 15, 2024 at the Putri Ayu Health Center Hall, in the form of group education for 70 minutes for 6 teenage pregnant mothers. The material was delivered using lecture, discussion and question and answer methods. Before and after education, tests were carried out using the same questionnaire. After being given education, there was an increase in average knowledge of 1.2 and attitude of 4.5 points. It was concluded that education is important for pregnant women in efforts to change behavior and is important to prevent perinatal depression.